'I get together with my friends and try to change it'. Young feminist students resist 'laddism', 'rape culture' and 'everyday sexism'. Issue 1 (2nd January 2018) - Lewis, Ruth; Marine, Susan; Kenney, Kathryn
Abstract: Contemporary alarm about 'laddism' reveals what feminist research and activism has long-recognised; universities, like other social institutions, can be dangerous places for women. Research in the US and, more recently, the UK reveals alarming rates of violence, against women, the cultural and institutional norms which support violence and gaps in institutional responses. In the midst of this contemporary alarm about the university as a hotbed of laddism, there is a risk that the university – a site of potential empowerment and liberation for women (and men) – becomes re-positioned as a danger zone. The limited focus on danger and safety belies the potential of universities to enhance human freedoms through intellectual endeavour. We argue this progressive potential should remain centre-stage, as should university-based resistance to everyday sexism and laddism. This paper analyses accounts of young women feminists ( n  = 33) in UK and US universities. It explores their use of feminism and features of the university environment to resist and challenge oppressive cultures and practices. It argues that, despite encroaching neoliberalism and enduring sexism, universities continue to provide environments for engagements with feminism, enabling young women students to use feminism to resist and challenge sexism and to envision their feminist futures.